ANALISIS KESULITAN BELAJAR MATEMATIKA PADA MATERI OPERASI HITUNG BILANGAN BULAT SISWA KELAS IV - Muthma'innah, M (Jurnal Ilmiah Ibtida, 2023)
This paper aims to describe the difficulty of learning mathematics for Grade IV Elementary School students in the subject of Integer Count Operations. The research method used in this research is mini qualitative descriptive research, namely by taking one sample who has difficulty learning mathematics, then interviewing his difficulties in the material to be described and analyzed. The results of the study showed that, in the material on integers, students experienced difficulties in solving problems related to multiplication and division of integers. This is because the formula is difficult for students to understand, especially those related to the multiplication and division of negative integers. This is a note for teachers to find the right model and not monotonous, such as the use of the discovery learning model in learning mathematics material on integer arithmetic operations.